The impact of traumatic experience on the socialization of adolescents - MATIASH-ZAIATS, Liudmyla; NOSOVA, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Despite a considerable number of studies in trauma psychology, there remains a lack of research focused on how traumatic experiences influence socialization during adolescence. Understanding how traumatic events affect the development of social connections, self-perception, and adolescents' ability to integrate into society is particularly pertinent.Results. The study identifies the crucial role of traumatic experience in shaping behavioral models and social adaptation in adolescents. Trauma alters not only an individual's psychological structure but also affects their perceptions of social norms and values and their ability to integrate into society. Traumatic experiences can result in social isolation, disruption of interpersonal relationships, and the emergence of antisocial or deviant behavior. Post-trauma socialization becomes a challenging process requiring specialized support and corrective measures. The study analyzed the characteristic features of traumatic experiences and their impact on social behavior, revealing specific changes in the perception of social roles and values that influence the socialization process after traumatic events.Conclusions. Traumatic experiences significantly affects the process of socialization in adolescents, determining their ability to integrate into society and adapt to social norms. Socialization after trauma involves overcoming internal conflicts, restoring social connections, and reintegrating into the social environment. The process of socialization depends on how well individuals can align their experiences with social norms and values, as well as on the support provided by social institutions. This emphasizes the importance of developing effective support and rehabilitation programs for adolescents who have experienced trauma.
Keywords: traumatic experience; socialization; adolescence; post-traumatic changes; social adaptation; deviant behavior